Assessment of academic readiness to achieve student success and retention - Visser, Herman; van Zyl, Dion (South African Journal of Higher Education, 2016)
Student retention and success in higher education is a major concern worldwide. Students are generally less prepared for higher education studies and more at risk of dropping out, stopping out or taking longer to complete their qualifications. A conceptual model serves as common point of reference to enhance student success, retention, graduation and satisfaction, and in particular the assessment of risk associated with academic readiness for higher education studies. The predictive correlations between average high school marks from the South African National Senior Certificate (NSC) and average marks in the first year of study at the University of South Africa are investigated with the intention of assessing aspects of academic readiness to identify associated risk and increase student retention and success. The correlations between first year marks and variables such as home language, language of study, age, gender, race, qualification level, type of National Senior Certificate and College were investigated.